2009
DOI: 10.1097/brs.0b013e31819a825d
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Neurological Deficit After Surgical Decompression of Symptomatic Vertebral Metastases

Abstract: Patients with neurologic deficit because of spinal bone metastases benefit from early operative intervention. Urgent surgery is indicated in patients with less than 3 days of neurologic deficit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 30 publications
0
14
1
1
Order By: Relevance
“…Hessler et al, operated on 194 patients with neurologic deficits due to spinal metastases and evaluated pre-operative and post-operative Frankel scores that were measured five to seven days after surgery. 15 They reported a significant correlation between the pre-operative duration of symptoms and the post-operative neurologic outcome (p<0.01, Kendall-τ b = −0.331), and patients with symptom duration of <10 days and <3 days having higher probability of neurologic improvement compared to patients with >15 days symptom duration. The duration of symptoms did not appear to correlate with the probability of neurologic deterioration.…”
Section: Resultsmentioning
confidence: 96%
“…Hessler et al, operated on 194 patients with neurologic deficits due to spinal metastases and evaluated pre-operative and post-operative Frankel scores that were measured five to seven days after surgery. 15 They reported a significant correlation between the pre-operative duration of symptoms and the post-operative neurologic outcome (p<0.01, Kendall-τ b = −0.331), and patients with symptom duration of <10 days and <3 days having higher probability of neurologic improvement compared to patients with >15 days symptom duration. The duration of symptoms did not appear to correlate with the probability of neurologic deterioration.…”
Section: Resultsmentioning
confidence: 96%
“…Chong et al [27] reported that 20% of their patients showed improvement of Frankel grade. One international multiple center study [21] showed that 64% of their cohort had improved or maintained their preoperative Frankel grade of Hessler et al [28] and found that 70% of their patients who underwent decompression within 24 hours achieved improved neurological function. The relative frequency of complications related to spinal metastatic surgery is high especially in the context of emergency surgeries.…”
Section: Other Surgical Outcomesmentioning
confidence: 97%
“…Patients with metastatic cancer are challenging to treat, because metastasis represents an advanced stage of the disease and, hence, is indicative of poor prognosis 1,2,3,9,18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Dorsal spinal decompression and stabilization are the most frequent surgical techniques used to treat metastatic disease of the thoracic and lumbar spine 1,2,3,4,5,6,7,8,9,10 . For patients with a solitary spinal metastasis without vertebral canal invasion and who are in good general health with a long life expectancy, tumor resection through en bloc spondylectomy/total vertebrectomy with primary stabilizing instrumentation has been suggested 9,10,11,12,13 . A recent paper reported that candidates for en bloc spondylectomy are not frequently encountered 14,15,16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation